2002
DOI: 10.1123/jtpe.22.1.86
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Bug-In-The-Ear Device on Intralesson Communication between a Student Teacher and a Cooperating Teacher

Abstract: This case study of a student teacher (ST) and her cooperating teacher (CT) employed an AB1B2A reversal design over an entire high-school-level student teaching practicum to determine the effect of a two-way, bug-in-the-ear radio device on dyadic intralesson communication characteristics, participant role satisfaction with the device, and attitude toward using the device and additional equipment. Likert-scale, postlesson questionnaires measured participant satisfaction with their roles, the communication, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 19 publications
1
39
0
1
Order By: Relevance
“…their motivation for acceptance of the CT role (Koerner, 1992;Mitchell & Schwager, 1993); the teaching perspectives that affect CT advisory practices (Clarke & Jarvis-Selinger, 2005); the strategies for success in the CT role (Sanderson, n.d.); the impact of CT task statements provided during postobservation conferences on the outcomes of student teacher lessons that are retaught (Coulon, 1991(Coulon, , 2000Coulon & Lorenzo, 2003); and the nature, quantity, and quality of feedback provided during postobservation/postlesson conferences (Christensen, 1988;Coulon & Byra, 1997;Freiberg & Waxman, 1988;Kahan, 2002;Kahan, Sinclair, Saucier, & Nguyen Calozzi, 2003;Wilkins-Canter, 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…their motivation for acceptance of the CT role (Koerner, 1992;Mitchell & Schwager, 1993); the teaching perspectives that affect CT advisory practices (Clarke & Jarvis-Selinger, 2005); the strategies for success in the CT role (Sanderson, n.d.); the impact of CT task statements provided during postobservation conferences on the outcomes of student teacher lessons that are retaught (Coulon, 1991(Coulon, , 2000Coulon & Lorenzo, 2003); and the nature, quantity, and quality of feedback provided during postobservation/postlesson conferences (Christensen, 1988;Coulon & Byra, 1997;Freiberg & Waxman, 1988;Kahan, 2002;Kahan, Sinclair, Saucier, & Nguyen Calozzi, 2003;Wilkins-Canter, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…What does exist deals primarily with experimental research about effects of the "mechanical third ear" or "bug in the ear" device used by Carmen Giebelhaus (1994) and others as a method by which student-teaching supervisors and C T s can provide immediate feedback and comment about student teacher lessons (see also, Giebelhaus & Cruz, n.d.;Kahan, 2002). The Giebelhaus research never attempts to describe or classify by nature the feedback provided to student teachers during lesson implementation, nor does it describe or categorize related CT behaviors; emphasis is on the reactions of those involved to the technology being tested.…”
Section: Introductionmentioning
confidence: 98%
“…Adding 2 hours of BIE training to a traditional in-service workshop resulted in changes to teachers' behavior management practices (Bowles & Nelson, 1976). Using the BIE promoted "withitness" and autonomy during student teaching (Kahan, 2002). Offering immediate feedback through the BIE device during instruction was more effective in increasing pre-service teachers' completion of three-term contingency trials than providing delayed feedback during a post-observation conference (Scheeler & Lee, 2002).…”
Section: Short-term and Longer Term Effectsmentioning
confidence: 99%
“…Between 1971 and 2008, we located five articles-one descriptive account (Herold et al, 1971), one experimental study (Bowles & Nelson, 1976), two single-subject investigations (Kahan, 2002;Scheeler & Lee, 2002), and one qualitative inquiry (Farrell & Chandler, 2008)-wherein the authors reported the short-term effects of BIE feedback delivered onsite. With onsite delivery, the BIE communication system used was wired or wireless; however, due to limited transmitting capabilities, the supervisor or coach was physically present in the classroom or school building when providing feedback through it.…”
Section: Short-term and Longer Term Effectsmentioning
confidence: 99%
“…Following each lesson, all teaching STs (n ¼ 21) completed a short Likert-scale inventory on satisfaction with the role of teacher, influence of communication on satisfaction with role, characteristics of the communication as well as satisfaction with the device. Coding of tape transcriptions after Kahan (2002) showed that the communication was shaped by the focus of the observation sheets. Means of the tabulated frequencies on each survey item indicated that the participants were overall very satisfied with the process of being coached.…”
mentioning
confidence: 99%